2019
DOI: 10.1002/cctc.201900890
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐Batch Photocatalytic Reduction of Nitrates: Role of Process Conditions and Co‐Catalysts

Abstract: Photocatalysis has been used to reduce nitrate ions from waste and drinking water. A semibatch photoreactor was developed for this process and commercial nanostructured TiO2 (P25) and TiO2 in nanosized form prepared by flame spray pyrolysis (FSP) were used as catalysts. Several noble metals were added as co‐catalyst on both titania samples and the chemical physical properties of every sample were studied by XRD, BET and UV‐Vis spectroscopy techniques. The optimum pH to reach the highest conversion of nitrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…The addition of some noble metals (e.g., Au) may also improve the light harvesting through the plasmonic effect. Furthermore, if metal addition is followed by thermal reduction in H 2 to reduce the metal, as reported, e.g., in [25], the presence of the metal itself can favor titania reduction during the activation in reducing environment, thus indirectly decreasing the titania band gap.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…The addition of some noble metals (e.g., Au) may also improve the light harvesting through the plasmonic effect. Furthermore, if metal addition is followed by thermal reduction in H 2 to reduce the metal, as reported, e.g., in [25], the presence of the metal itself can favor titania reduction during the activation in reducing environment, thus indirectly decreasing the titania band gap.…”
Section: Introductionmentioning
confidence: 67%
“…Indeed, the further increase of the rate of ammonia oxidation for pH higher than 9 indicates that electrostatically favored adsorption is not the rate-limiting step (Figure 5). Considering the negatively charged surface of both TiO 2 samples at high pH (9 and 11.5) and simultaneously the higher fraction of NH 3 with respect to NH 4 + at pH 11.5 than 9, it is suggested that for both P25 and FSP photocatalysts, the photooxidation of ammonia should be preferentially mediated by oxidizing radicals OH, as recently discussed [25]. neutral NH with respect to NH may explain the higher initial rates at pH 11.5 than at pH 9.0 (Figure 5).…”
Section: Effect Of Phmentioning
confidence: 78%
See 2 more Smart Citations
“…5.6). Based on ζ-potential measurement, the point of zero charge of the P25 sample resulted 6.5, suggesting a slight positive charge of the surface under the operating conditions [41]. Furthermore, dynamic light scattering (DLS) showed that the average size of suspended particles ranged negligibly from 126 to 135 when passing from pH 3.5 to 11 [42].…”
Section: Catalytic Activitymentioning
confidence: 99%